Implementation of tobacco control policy at the local level in Thailand: Performance evaluation and associated factors - Phetphum, Chakkraphan; Keeratisiroj, Orawan; Wangwonsin, Artittaya; Jariya, Wutthichai (Tobacco induced diseases, 2025)
Tobacco use is one of the top five risk factors for disability-adjusted life years globally, including Thailand. Consequently, Thailand has enacted the Tobacco Products Control Act in alignment with the World Health Organization Framework Convention on Tobacco Control. To facilitate national tobacco control policies at the local level, Provincial Tobacco Products Control Committees (PTPCCs) have been established in all 77 provinces. This study aimed to assess the performance of PTPCCs in implementing the tobacco control policy and to identify its associated factors. This cross-sectional survey utilized a self-reported online questionnaire to collect data between May and August 2023. The target population comprised secretaries of PTPCCs across 77 provinces. The survey achieved a completion rate of 75.32%, with responses from 58 provinces. Among the 58 responding provinces, 53% achieved the law enforcement indicator, 43% met the target for prevention of new smokers, and only 34% achieved the smoking cessation performance. Multiple logistic regression analysis revealed that adequate access to policy information was strongly associated with achieving law enforcement (AOR=10.53; 95% CI: 1.20-92.23). The availability of adequate media resources was significantly associated with successful prevention of new smokers (AOR=8.64; 95% CI: 2.09-35.67). Stronger characteristics of implementing agencies - referring to the provincial governor's commitment to tobacco control policy and the engagement of public and private stakeholders - were positively associated with smoking cessation performance (AOR=2.05; 95% CI: 1.13-3.71). PTPCCs should be strengthened through adequate access to policy information, sufficient media resources, and strong provincial leadership with multi-sectoral engagement, as these factors are critical to effective policy performance. Enhancing these components will improve the implementation of tobacco control policy at the local level.